2023
DOI: 10.1021/jacs.3c06794
|View full text |Cite
|
Sign up to set email alerts
|

Three-Component Cross-Electrophile Coupling: Regioselective Electrochemical Dialkylation of Alkenes

Lingxiang Lu,
Yi Wang,
Wendy Zhang
et al.

Abstract: The cross-electrophile dialkylation of alkenes enables the formation of two C(sp 3 )−C(sp 3 ) bonds from readily available starting materials in a single transformation, thereby providing a modular and expedient approach to building structural complexity in organic synthesis. Herein, we exploit the disparate electronic and steric properties of alkyl halides with varying degrees of substitution to accomplish their selective activation and addition to alkenes under electrochemical conditions. This method enables… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 67 publications
0
13
0
Order By: Relevance
“…98 Lu et al employed the same strategy in a three-component cross-electrophile coupling reaction. 111 Both Mg(ClO 4 ) 2 and MgBr 2 are poorly soluble in THF, which was used as the reaction medium, but linear ethers and diethers chelate more strongly to the Mg 2+ ions and solubilize Mg salts. 119,120 As described above, TPPA plays a similar role in supporting Mg sacrificial anode oxidation in THF; a passivating salt layer forms on the anode in the absence of TPPA but does not prevent Mg oxidation when TPPA is present.…”
Section: Passivation By Products Formed During Anodic Strippingmentioning
confidence: 99%
See 1 more Smart Citation
“…98 Lu et al employed the same strategy in a three-component cross-electrophile coupling reaction. 111 Both Mg(ClO 4 ) 2 and MgBr 2 are poorly soluble in THF, which was used as the reaction medium, but linear ethers and diethers chelate more strongly to the Mg 2+ ions and solubilize Mg salts. 119,120 As described above, TPPA plays a similar role in supporting Mg sacrificial anode oxidation in THF; a passivating salt layer forms on the anode in the absence of TPPA but does not prevent Mg oxidation when TPPA is present.…”
Section: Passivation By Products Formed During Anodic Strippingmentioning
confidence: 99%
“… 98 Lu et al observed similar passivation of the Mg sacrificial anode in an electrochemically driven three-component cross-electrophile coupling reaction; though conversion of the starting material exceeded 95%, the desired product was obtained in low yields due to the growth of a thick passivating film at the anode and accompanying high cell voltage. 111 Anode passivation can also be influenced by seemingly unrelated components. In the electroreduction of epoxides, Huang et al employed tripyrrolidinophosphoric acid triamide (TPPA) as a cosolvent to improve the solubility of the LiCl supporting electrolyte in THF and to prevent cathodic reduction of the sacrificial metal cations.…”
Section: Passivation By Products Formed During Anodic Strippingmentioning
confidence: 99%
“…With the renaissance of photo- and electrochemistry in organic synthesis, great achievements have been made in two-component reductive cross-couplings while avoiding the requirement of metal powders . Despite these success, multicomponent reductive cascade reactions are still less well-developed. , Recently, Martin and Mao independently disclosed 1,2-alkylarylation of activated alkenes via nickel/photoredox dual catalysis with organic reductants (Scheme a) . On the other hand, Yue and Rueping successfully realized nickel-catalyzed stereoselective alkylarylation of alkynes with amine reductants by switching between electrochemistry and photocatalysis (Scheme b) …”
mentioning
confidence: 99%
“…Although the electrochemical difunctionalization of alkenes, especially styrenes, has been developed, the reductive diarylation of 1,3-dienes under electrochemical conditions has not been well developed yet. Based on our long-term study of electrochemical nickel-catalyzed coupling, we envisioned that the activation of aryl halides through cathodic reduction and nickel catalyst could realize the desired cross-coupling. Herein, we developed a regioselective diarylation of 1,3-dienes through Ni electrocatalysis without additional ligands and reductants (Scheme D).…”
mentioning
confidence: 99%